Nutritional and Lifestyle Determinants of Cardiovascular Disease Risk Among Adolescents: A Structured Narrative Review - Mohammad Zainul Ma’arif; Riezky Faisal Nugroho; Alfan Ridha (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: Cardiovascular disease remains the leading cause of death worldwide, and its pathogenesis begins early in adolescence through the development of cardiometabolic risk factors. Changes in dietary habits, low physical activity, sedentary behavior, alcohol consumption, and high intake of ultra-processed foods contribute to the potential for increased cardiovascular risk in adolescents. Aim: This study aimed to review the influence of nutritional and lifestyle factors on cardiovascular disease risk among adolescents. Methods: A structured narrative review was conducted through a literature search in PubMed/MEDLINE. Articles published between 2020 and 2026 were screened based on predefined inclusion and exclusion criteria. Seven studies met the eligibility criteria and were included in the final synthesis.. Results: The findings showed that poor-quality dietary patterns characterized by high consumption of ultra-processed foods, sugar, saturated fat, and sodium were associated with obesity, insulin resistance, hypertension, dyslipidemia, and increased cardiometabolic risk. Alcohol consumption contributed to elevated triglycerides, LDL levels, and impaired lipid metabolism. Furthermore, sedentary behavior and low physical activity were associated with impaired cardiac function, increased inflammation, and early vascular changes in adolescents. Conclusion: Nutritional and lifestyle factors play a significant role in the early development of cardiovascular disease risk during adolescence. Early interventions focusing on improving diet quality, increasing physical activity, reducing sedentary behavior, and limiting alcohol consumption are essential to prevent future cardiovascular disease.